2021
DOI: 10.1002/ceat.202000508
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Preparation of a Gel Polymer Electrolyte Membrane for Supercapacitors

Abstract: Supercapacitors have great potential in the hybrid fuel automobile market because of their high power density and fast charge and discharge, in which the working electrolyte of supercapacitors is the key to determine their performance. Optimization and preparations of poly(vinylidene difluoride)‐hexafluoropropylene/poly(methyl methacrylate) (PVDF‐HFP/PMMA) gel polymer electrolyte membranes for supercapacitors based on Design Expert 8.0 software are described. The range of conditions is determined by monofactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In addition, Figure d shows the Ragone plots of the supercapacitor, exhibiting the highest power density of 2139.1 W kg –1 at an energy density of 15.9 Wh kg –1 and the largest energy density of 28.2 Wh kg –1 at the power density of 280.1 W kg –1 . One may note that the specific capacitance, energy density, and power density of the present Na-ion conducting polymer electrolyte (GPE/Na-3) membrane-based supercapacitor is well comparable with the reported ones. All these demonstrate that the Na-ion supercapacitor possesses a promising capacitive performance. The cyclic life of a supercapacitor is an importance parameter for practicability.…”
Section: Results and Discussionsupporting
confidence: 79%
“…In addition, Figure d shows the Ragone plots of the supercapacitor, exhibiting the highest power density of 2139.1 W kg –1 at an energy density of 15.9 Wh kg –1 and the largest energy density of 28.2 Wh kg –1 at the power density of 280.1 W kg –1 . One may note that the specific capacitance, energy density, and power density of the present Na-ion conducting polymer electrolyte (GPE/Na-3) membrane-based supercapacitor is well comparable with the reported ones. All these demonstrate that the Na-ion supercapacitor possesses a promising capacitive performance. The cyclic life of a supercapacitor is an importance parameter for practicability.…”
Section: Results and Discussionsupporting
confidence: 79%
“…It was also found that the discharge time was much longer than that of the PVA-SA-Na 2 SO 4 supercapacitor due to the additional contribution of the K 3 [Fe(CN) 6 ] reversible redox process. Moreover, the GCD curves show small iR drop values demonstrating a prime feature of reversible capacitance and small internal resistance [54].…”
Section: Electrochemical Performance Of the Pva-sa-fe 3+ -Na 2 So 4 G...mentioning
confidence: 96%